Stability of B50 biodiesel added with glycerol ester additive based on palm oil oleic acid: - Firda Dimawarnita; Yora Faramitha; Erliza Hambali (Menara Perkebunan, 2023)
Biodiesel in Indonesia is a mixture of Fatty Acid Methyl Ester (FAME) and diesel oil. Mixing FAME and diesel oil is challenging since FAME is separated from diesel oil at low temperatures. Changes in the physico-chemical properties of biodiesel during storage decrease biodiesel quality due to dissolved oxygen, potentially damaging the engine. Using glycerol ester (GE) as an additive can be an alternative solution to tackle that problem. This research examined the stability of GE-added biodiesel. As a comparison, commercial diethyl ether (DEE) additive was used. The concentration of additive added to biodiesel varied at 1000, 2000, and 3000 ppm while the storage temperature varied at 12, 25, and 42℃. The stability of biodiesel was evaluated for three months by measuring the acid value, viscosity, corrosion rate, and water content. The acid values ​​​​of the various types and concentrations of additives still meet the SNI 7182-2015 standard (0.5 mg KOH g-1 sample) with a value range of 0.148-  0.392 mg KOH g-1 sample. Kinematic viscosity had a value range of 3.12-3.58 cst, which also meets the SNI 7182-2015 standard (2.3-6 cst). The highest corrosion rate for GE and DEE was in the first week, with values of 0.447 and 0.261 mpy, respectively. Both B50 biodiesel control and the addition of 1000 ppm GE had the same water content value on the 18th day, which was 0.046%, and this value was considered the highest water content. This means adding an additive can maintain the water content in B50 biodiesel. Overall, GE additives in B50 biodiesel with various concentrations comply with SNI 7182-2015 standard.